Community Organizing and the Effectiveness of Health Programmes in Rural Udo Community of Edo State in South-South Nigeria - Ernest Osas Ugiagbe; Helen Eweka (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This study examines the nexus between community organizing in the context of social solidarity/consciousness and the effectiveness of health programmes in the Udo rural community in Edo state, Nigeria. The survey research design was adopted, and the sampling technique was simple random in the selection of participants. Ten villages were randomly selected where 200 participants were randomly administered the questionnaire. The data collected were analyzed with chi square, and the results show that social consciousness, solidarity and the leadership of the Iyase of Udo contribute immensely to the success of health programmes in Udo community. Received 21th December 2017; Revised 24th December 2018; Accepted 10thApril 2019